Investigating the Protective Role of N-Acetyl Cysteine and S-Methyl Cysteine in the Activity of Antioxidant Enzymes and the Level of lipid Peroxidation Due to Acetamiprid Administration in Rat Kidney and Serum - Nazanin Khovarnagh; Bagher Seyedalipour; Ali taravati (Fasa University of Medical Sciences, 2020)
Background & Objective: Acetamiprid (ACP), as a neonicotinoid toxin, causes free radicals production and oxidative stress in various organisms. The aim of this study was to evaluate the antioxidative effects of N-acetylcysteine (NAC) and S-methylcysteine (SMC) on reducing acetaminoprid-induced oxidative stress in serum and kidney of rats. Materials & Methods: In this experimental study, 42 male Wistar rats were randomly divided into 6 groups of 7 including one control, one sham (normal saline) and five experimental groups, which intra-peritoneally received ACP (5 mg/kg), NAG (160 mg/kg), SMC (100 mg/kg), ACP+NAC, ACP+SMC, and ACP+ NAC+SMC for one week. After separation of serum and kidney tissue, the activity of the catalase (CAT), glutathione S-transferase (GST), glutathione concentration (GSH), malondialdehyde (MDA) and total antioxidant (TAC) was determined. Results: Acetamiprid caused significant increase in GST activity in serum and kidney (p< 0.01), CAT activity in serum and kidney (p< 0.05) but insignificant increase in MDA level and insignificant decrease in GSH and TAC compared to control. NAC and SMC, alone and in combination with ACP, restored the levels of TAC, GSH and MDA and activities of CAT and GST. Conclusion: Acetamiprid increases lipid peroxidation, activity of CAT and GST, and decreases the concentration of GSH and TAC, presumably by producing free radicals. Administration of NAC and SMS as antioxidants causes a decrease in acetamiprid toxicity due to relative reduction of free radicals.